Usability Analysis of a Collective Digital Memorial System: Between Technique and Emotion - Ferreira Monteiro, Luís Flávio; Maciel, Cristiano; Pereira, Vinícius Carvalho; Lima, Fernanda (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2025: Anais do XXIV Simpósio Brasileiro sobre Fatores Humanos em Sistemas ComputacionaisDO - 10.5753/ihc.2025.10882, 2025)
Introduction: Although digital memorials have been discussed conceptually for over a decade, there remains scant evidence on the user experience of collective digital memorials, platforms where honorees share a common bond. Objective: To fill this gap by conducting a mixed-methods usability evaluation of a web-based collective memorial. Methodology: Eight participants, varied in age, gender, and technical familiarity, completed representative tasks while their interactions were recorded via screen capture, think-aloud protocol, and preand post-test questionnaires. Results: Analysis uncovered recurring challenges in onboarding, feedback, and cultural representativeness that critically shape the user experience. Based on these findings, three grief-oriented heuristics are proposed to extend Nielsen’s usability principles with considerations specific to posthumous memory. All data and a replication package are publicly available to support further research.